Molecular bases of aberrant miR‐182 expression in ovarian cancer. Issue 11 (12th July 2016) - Marzec‐Kotarska, Barbara; Cybulski, Marek; Kotarski, Józef Czesław; Ronowicz, Anna; Tarkowski, Rafał; Polak, Grzegorz; Antosz, Halina; Piotrowski, Arkadiusz; Kotarski, Jan
Abstract : The molecular bases of miR‐182 deregulation in epithelial ovarian cancers (EOCs) remain unknown and its diagnostic or prognostic role in EOCs is still unclear. We performed miR‐182 expression analysis using a microarray approach and real‐time PCR (qPCR). We also used array comparative genomic hybridization and methylated DNA immunoprecipitation to study copy number changes and methylation aberrations within coding locus/promoter sequences of miR‐182 in EOC tissues, respectively. We have found that miR‐182 expression is significantly increased in EOC ( P  < 0.00001) and that higher miR‐182 expression in EOC is linked with significantly shorter overall survival ( P  = 0.026). The methylation of miR‐182 promoter was significantly associated with lower miR‐182 expression in EOC tissues ( P  = 0.045). miR‐182 over‐expression is connected with copy number (CN) gains of this miRNA coding sequences in EOC ( P  = 0.002), and the number of PRDM5 copies is significantly and inversely correlated with miR‐182 expression evaluated by qPCR ( R  = −0.615, P  = 0.009). We conclude that the aberrant miR‐182 expression in EOC may be due to CN gains within its coding locus. The miR‐182 promoter is rarely methylated in EOC, and its methylation status is associated with lower miR‐182 expression. Deletion of the PRDM5 locus may play a supportive role in miR‐182 overexpression in EOC. miR‐182 is an unfavorable prognostic factor in EOC. © 2016 Wiley Periodicals, Inc.